2019
DOI: 10.1111/ijd.14392
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy‐induced skin toxicity and capillary leak syndrome

Abstract: Background The occurrence of chemotherapy‐related adverse cutaneous reactions in the setting of capillary leak syndrome (CLS) is quite rare. Our objective was to identify the type of skin reactions associated with CLS. Methods Leukemia or hematopoietic stem cell transplant patients between January 2010 and December 2017 were identified, and medical records were reviewed for a dermatology consultation occurring concomitantly with CLS. Results Five patients were identified, two with a diagnosis of toxic erythema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The main differences, as suggested in such as dialysis to extract the causative drug can be life-saving to these patients as described previously. 5,6 No statistically significant histopathological marker of SJS or TEN was identified in our study ( The triggers identified in our study, including medications and pathogens, were similar to those reported previously. 4,7 Our patients underwent standard treatment approaches as reported previously, including supportive care, IVIG, and steroids.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The main differences, as suggested in such as dialysis to extract the causative drug can be life-saving to these patients as described previously. 5,6 No statistically significant histopathological marker of SJS or TEN was identified in our study ( The triggers identified in our study, including medications and pathogens, were similar to those reported previously. 4,7 Our patients underwent standard treatment approaches as reported previously, including supportive care, IVIG, and steroids.…”
Section: Methodssupporting
confidence: 88%
“…Death is usually caused by resulting multi‐organ damage. Early and rapid mechanisms such as dialysis to extract the causative drug can be life‐saving to these patients as described previously 5,6 …”
Section: Discussionmentioning
confidence: 99%